Microcorona Discharge-Mediated Nonthermal Atmospheric Plasma for Seed Surface Modification - Teerakawanich, Nithiphat; Kasemsuwan, Varakorn; Jitkajornwanich, Kulsawasd; Kanokbannakorn, Weerawoot; Srisonphan, Siwapon (My University, 2018)
By exploiting the physical effect of a highly nonuniform localized electric field and electron-initiated impact ionization on space charge, we generated homogeneous nonthermal plasma under ambient atmosphere. We evaluated the physical characteristics and evolution of microcorona discharge-induced nonthermal atmospheric plasma (NAP) based on a point-to-plane electrode in open air with two distinct configurations. High-voltage pulses were employed as the primary power source of corona discharge generation to reveal the fundamental mechanism, polarity effect and feasibility of using NAP for organic surface modification. Consequently, we employed NAP to modify the surface of rice (Oryza sativa L.) seeds to improve their wettability. The surface modification of the rice seeds was investigated via water apparent contact angle (ACA) and water imbibition (WI) measurements. The ACA and WI measurements revealed not only the improvement in the wetting properties but also the mutual relationships between and limitations of ACA and WI analysis. We found that the WI time reached saturation after a certain treatment time, called the threshold treatment time. Because vacuum conditions are not required, well-established NAP technology will garner interest in many fields, ranging from the life, environmental, and biomedical sciences to solid-state electronics applications.
Keywords: Electron-initiated impact ionization; Microcorona discharge; Nonthermal atmospheric plasma; Surface modification; Wettability